Limescale and corrosion in steam boilers. Requirements for feed and boiler water quality - Marjanowski, Jan (Instal, 2020)
The aim of this paper is to present problems connected with exploitation of steam boilers with pressure up to 20 bars. Reasons of boiler scaling and corrosion are described. Particular emphasis is put on the quality of steam boiler feed water, on desalting pro blems, water and heat savings.